Conservation and Utilization of Summer Crops Biodiversity in Nepal - Joshi, Bal Krishna; Ghimire , Krishna Hari; Karkee, Ajay; Mainali, Ram Prasad; Thapa, Pradip; Bhattarai, Mukunda (Agriculture Development Journal, 2024)
Nepal faces a pressing challenge with the alarming loss of around 50% of its summer crop genetic resources (SCGRs) and the endangerment of native landraces. To combat this decline, the national genebank in Nepal has developed 101 good practices for agricultural genetic resources (AGRs) conservation and utilization. Red zoning and red listing strategies aid in identifying conservation priorities. The Genebank collaborates with stakeholders to collect, characterize, and promote SCGRs, resulting in 6177 accessions representing 71 summer crop species stored in Seed Banks. Diverse conservation repositories include genebanks, tissue banks, DNA banks, community genebanks, school field genebanks, and agro-gene sanctuaries. In 2022, 724 accessions of 20 summer crops were distributed for research, while the registration of 19 landraces after genetic enhancements led to their inclusion under the National Seed Board. The free distribution of germplasm accelerates its utilization, further facilitated by online access. The genebank also promotes agro-insect field genebanks recognizing the importance of agro-insects and pollinators in biodiversity conservation. To maintain native SCGRs, value additions are emphasized, underlining the need to actively enhance genetic diversity in agricultural fields. These comprehensive measures underscore Nepal’s commitment to safeguarding agrobiodiversity, ensuring food security, and bolstering agricultural resilience to climate and other stresses.